Territory Posts and Telecommunications under Investigation - Corejova, Tatiana (Communications - Scientific letters of the University of Zilina, 2002)
The following factors have a significant influence upon the servicing of the area from the aspect of the postal and telecommunication infrastructure and services: increase in demand for postal and telecommunication products, changes in the demand distribution according to particular ways of connection, or change in market shares, environmental influences which represent the continuing tendency of demand transmission after transmission of information from the postal infrastructure to telecommunication infrastructure – from the fixed networks to the mobile networks – devices, and dynamic rise in the Internet market. Besides the technological development, the following factors are important from the aspect of the observation of the demand for the postal and telecommunication products: the space ones – centers; regional centers are more efficient, innovative, economically more developed, which is also connected with a higher level of the postal and telecommunication infrastructure, and with higher requirements on this infrastructure, the institutional and economic ones that now include, within the Žilina region, especially the integration processes within the Beskydy region (development of the cross-border cooperation), decreasing the use of subsidy tools of the regional policy, and deregulation of many branches and activities, the social-psychological ones that reflect and include the problems of life-style, employment, income groups, housing type, and so on. From the aspect of the demand for the postal and telecommunication products, they are important and they influence the type and the volume of required products, networks, etc.